2015
DOI: 10.12740/pp/27538
|View full text |Cite
|
Sign up to set email alerts
|

The concept of alcohol craving.

Abstract: The aim of the article was to assess how the perception of alcohol craving, which is one of the symptoms of alcohol dependence, evolved, as well as how it was reflected in the diagnostic classifications. The purpose of this article was also a discussion of the models of the origins of craving, explaining the etiology of this phenomenon and the tools for measuring this concept. The concept of craving, defined as a strong need or compulsion to drink alcohol, functioned for many years, not only in the clinical pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
0
5
0
1
Order By: Relevance
“…Thus, they may provide an opportunity to examine specific mechanisms purported to lead to drinking in the general population—although it remains unclear if factors leading to alcohol use in college students occur similarly in other groups. For example, alcohol craving is widely regarded as a mechanism that leads to alcohol consumption (Iwanicka & Olajossy, 2015; Lowman et al, 2000; McHugh et al, 2016), yet some research has reported that due to the episodic nature of college drinking, situational factors like the day of the week likely play a more predominant role in consumption behavior (Kuntsche & Labhart, 2012). However, given a growing body of work in idiographic science, evidence points to the likelihood that, even within this population, the relationship between mechanisms such as craving and alcohol consumption will differ from person to person.…”
Section: College Drinkingmentioning
confidence: 99%
“…Thus, they may provide an opportunity to examine specific mechanisms purported to lead to drinking in the general population—although it remains unclear if factors leading to alcohol use in college students occur similarly in other groups. For example, alcohol craving is widely regarded as a mechanism that leads to alcohol consumption (Iwanicka & Olajossy, 2015; Lowman et al, 2000; McHugh et al, 2016), yet some research has reported that due to the episodic nature of college drinking, situational factors like the day of the week likely play a more predominant role in consumption behavior (Kuntsche & Labhart, 2012). However, given a growing body of work in idiographic science, evidence points to the likelihood that, even within this population, the relationship between mechanisms such as craving and alcohol consumption will differ from person to person.…”
Section: College Drinkingmentioning
confidence: 99%
“…(Bohn et al 1995) was used to measure the current urgency of drinking during withdrawal. This scale is one of the most important tools used to measure craving, both in clinical trials and therapeutic practice (Iwanicka and Olajossy 2015). Total AUQ scores between 8-56, with greater values indicating a greater urge to drink alcohol.…”
Section: Scale Assessments At Baselinementioning
confidence: 99%
“…One line of evidence suggests that a higher level of craving at the time of hospitalization is associated with relapse following residential addiction treatment (Oslin et al 2009). Other studies also support the role of craving in relapse and the utility of evaluating craving with tools such as the visual analog scale (VAS) and alcohol urge questionnaire (AUQ) in assessing relapse risk (Iwanicka and Olajossy 2015;Schneekloth et al 2012). Furthermore, negative emotional states conduce to cue-elicited craving, particularly in individuals who drink to alleviate depression and anxiety (Pombo et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Doświadczanie głodu alkoholu jest istotnym elementem zaburzeń związanych z używaniem alkoholu. Wiele osób podejmujących leczenie lub będących w procesie nawrotu potwierdzało występowanie silnej, natrętnej potrzeby napicia się [11][12][13]. Głód alkoholu jako subiektywnie doświadczane zjawisko jest niezwykle trudny w definiowaniu.…”
Section: Komentarzunclassified